The Environment, Life Expectancy and Growth in Overlapping Generations Models: A Survey - Anna Dugan; Alexia Prskawetz; Natacha Raffin (TU Wien, Institute of Statistics and Mathematical Methods in Economics, Research Unit in Economics, 2022)
It is widely accepted that environmental and demographic changes will significantly influence the future of our society. In recent years, an increasing number of studies has analyzed the interlinkages among economic growth, environmental factors and a specific demographic variable, namely life expectancy, applying an overlapping generations framework. The aim of this survey is threefold. First, we review the role of life expectancy and pollution for sustainable growth. Second, we discuss the role of intervening factors like health investment and technological progress as well as institutional settings including government expenditures, tax structures and inequality. Finally, we summarize policy implications obtained in different models and compare them to each other.
Keywords: O11; O44; Q56; Q58; J10; 330; Environmental quality; Pollution; Longevity; Endogenous growth; Government policy